(untitled) (Tanzania Medical Journal, 2024)
Background Urethral stricture results from urethral fibrosis leading to bladder outlet obstruction. The most common signs include reduced urinary volume, urgency, dysuria, incontinence, lower abdominal pain, urethral discharge, blood in the semen and/or urine and recurrent urinary tract infections (UTI) due to post void residue. It imposes a great burden on the quality of life in men. There is paucity of literature in Tanzania on urethral stricture, therefore this study aimed to determine its prevalence, causes and characteristics in terms of the commonest site affected, the management options used and the most common complications occurring in the patients for a period of five years in order to have an insight on the pattern of the disease over the years. Broad Objective To determine the prevalence of operated urethral stricture disease, its etiology and characteristics including the commonest site affected, commonest investigation and treatment options used as well as the most common complications developed at Muhimbili National Hospital (MNH) from the year 2012 to 2016. Methodology A descriptive retrospective cross-sectional study was conducted at MNH whereby all the patients operated for urethral stricture from 2012 to 2016 were included. Data was collected from the files of the patients at the medical records after obtaining an ethical clearance. Data was analyzed by Statistical Package for Social Sciences version 20. Data were presented by using tables and histograms which showed the prevalence of urethral strictures operated at MNH from 2012 to 2016, the most common causes, the commonest location, the commonest complications seen, the most frequent investigations as well as the surgical treatment options used. The results enable us to see the pattern and the findings from one year to another. Result A total of 4170 patients were admitted for various urological pathologies from 2012-2016. Among these, 646 (15.5%) were operated for urethral strictures. Out of the 646 urethral stricture cases, only 303 (46.9%) files could be obtained from the records and were included in the study. Majority of the study population were aged 60 years and above. Almost all patients (99.7%) were males. The most common cause of the urethral stricture was seen to alternate between trauma, iatrogenic and infectious cause whereby the cause was seen to change from year to year. Bulbar urethra was the most frequent site affected. Urinary retention was the most common complication over the years except for the first year where UTI was reported to be the highest. Urethrogram was most commonly used for the diagnosis and direct vision internal urethrotomy (DVIU) was most frequently performed for the treatment of urethral stricture in these five years. Conclusion The prevalence of urethral stricture cases that were operated within the five-year period ranged from 15.1% to 17.3%. It was most commonly seen in the older age group. The cause was seen to be alternating between trauma, iatrogenic injury and infections within the five-year period. Bulbar urethra was the most commonly affected site with urinary retention and recurrent UTI being the commonest complications. Urethrogram was most commonly used for the diagnosis and the commonest surgical procedure done was DVIU.